LEADER OF CHANGE BASED ON THE PERCEPTIONS OF THE BUGIS AND MAKASSAR COMMUNITIES - Wustari L Mangundjaya; Resekiani Mas Bakar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Nowadays, the organization can be called a boundaryless organization, as moving from one organization to another and from one place to another is inevitable. In this regard, understanding the condition and characteristics of a society and culture is a must for a leader. A leader, especially a change leader, has to understand the culture, as he or she has to influence subordinates to follow the organization's objectives, without employees' commitment and support, the organizational change will be hard to achieve. Meanwhile, Indonesia consists of thousands of islands with various ethnics and cultures, making Indonesia a very diverse country, which then makes a leader should have an understanding of the characteristics of the people in the organization. The ethnic of Bugis-Makassar is the majority of the ethnic who stay in Makassar city. This study uses a qualitative approach with FGD as the tool in data collection. The number of participants is 30. The results show that the majority of the participants prefer to have a leader with the role of Coach compared with the other two roles. This result is expected to have contributed to the change leader that will be assigned in the organization with the majority of people from Bugis-Makassar.